Hammershus Castle - "Good Practices" and Managing Permanentl Ruin - Siwek, Andrzej; Trafas-Wołoszyn, Magdalena (Protection of Cultural Heritage, 2018)
Hammershus is a medieval Danish castle on the Bornholm island. In 1743 Hammershus was finally abandoned as a stronghold. The fortress was partially demolished around 1750. The ruins were put on the national historic register in 1822. From 1885, until his death in 1928, P. C. Hauberg was in charge of the extensive restoration work. After that, the castle remained a picturesque ruin. The conservation policy, which was taken from 1907, includes the purchase of land around the castle and systematic removal of the surrounding buildings. In 1969 Jørn Utzon created the concept of the information center hidden in the landscape. In 2013, his concept was implemented. The project was developed by the Danish team Arkitema, in cooperation with Buro Happold, and Ch. Harlang. The modern information center put into use in 2018. Building is removed from the ruins and hidden in the nearby slope. The protection of Hammershus Castle is subordinated to preserving its historical form - a permanent ruin. It is also conducted in the landscape sphere. The new reception center was located and designed so as to not compete with the historical ruin and landscape. The Hammershus castle management model is an example of good practice in protecting cultural heritage and historic ruins. The main point is to use the attractiveness of the historical ruins, as an object that attracts visitors.The remoteness of modern commercial functions from the monument create new possibilities for contemplating the castle ruins and contributes to strict landscape protection.